PERAN KEGIATAN ADMINISTRASI DAN DIGITALISASI DOKUMEN DALAM MENDUKUNG OPERASIONAL PADA BAGIAN KONSUMER BISNIS DI PT. BANK RAKYAT INDONESIA (PERSERO) TBK. KANTOR CABANG PALANGKA RAYA - Jessica Septiana Harto; Berta Margareta Agustin Wijaya (Jurnal Pengabdian Masyarakat Berkelanjutan, 2026)
This community service program aims to analyze the role of administrative activities and document digitization in supporting smooth operations in the Consumer Business Section at PT. Bank Rakyat Indonesia (Persero) Tbk. Palangka Raya Branch Office. The program focus includes physical records management (BRImen), document scanning processes, credit administration, and banking bureaucratic flows. This activity uses a descriptive qualitative approach with a participatory case study design through the Independent Impact Internship program. Primary data was obtained through in-depth observations and daily logbook records during the period 22 January to 22 May 2026. The program results show that orderly administration in support units (back-office) is the main determinant of the smooth running of services at the front line (front-office). The implementation of physical arrangement of documents into BRImen folders accompanied by digitization of files has proven to be effective in speeding up the information retrieval process, minimizing administrative errors, and expediting the distribution of authorization files (ACC) to the teller section. However, the high volume of archives, time-consuming manual searches, and incomplete customer documents are still operational obstacles that often delay service. Therefore, standardization of file verification and continuous integration of digitalization systems are crucial solutions to increase efficiency and quality of service.